Proposal of the Commitee for the General Practice of the Medical and Dental Professional Board: The future of the family medicine - SAFPJ Editor (South African Family Practice)
In the light of the transformation of the health care sciences in South Africa with a shift towards primary care and the consequent requirements of change in health care delivery, as well as the changing health care requirements of the population, this committee decided to pursue its mandate of improving general practice in South Africa by initiating a project on how training for general and family practice should be changed to meet these needs.